Astragalus polysaccharide protects sepsis model rats after cecum ligation and puncture - Li, Jun; Zhao, Jie; Chai, Yihui; Li, Wen; Liu, Xiaoqing; Chen, Yunzhi (Frontiers in Bioengineering and Biotechnology, 2022)
To investigate the protective effect and mechanism of Astragalus polysaccharide (APS) on septic rats, the present project applied APS at concentrations of 400, 600, and 800 mg/kg/d to rats for prophylactic administration for 7 d and a rat sepsis model was constructed by cecum ligation and puncture (CLP) method. Forty-eight rats were divided into six groups of eight each. Each experiment was repeated at least three times. Rat serum levels of VD3, 25(OH)D3, 1,25(OH)2D3, IL-6, TNF-α, CRP, sICAM-1, corticosterone (CORT), and short-chain fatty acids (SCFAs) in each group were detected, and renal damage was observed by H&E. We also determined the protein expression of CYP27B1, CYP24A1, vitamin D receptor (VDR), steroidogenic acute regulatory protein (STAR), 3β-hydroxysteroid dehydrogenase (3β-HSD), CYP21A2, CYP17A1, and CYP11B1. An operational taxonomic unit (OTU) was used to determine the gut microbiota diversity of septic rats after prophylactic administration and before modeling. Results revealed that APS markedly increased the contents of 25(OH)D3 and 1,25(OH)2D3, but greatly decreased those of TNF-α, IL-6, CRP, sICAM-1, and CORT. APS alleviated renal tubular dilation and vascular congestion in rat kidneys and substantially reduced renal cell apoptosis. Moreover, the expression of CYP24A1, VDR, CYP11B1, CYP21A2, CYP17A1, STAR, and 3β-HSD in kidneys of H-APS group were substantially decreased versus model group, whereas CYP27B1 was markedly increased. GC-MS detection indicated a substantial increase in SCFAs and acetic acid content in H-APS group versus model group. Through 16S sequencing, the abundance of genus and gut microbiota species increased in the APS groups compared to the control group. Taken together, APS increased the activity of vitamin D axis, inhibited the production of inflammatory factors in the body, altered the structure of rat intestinal flora, and increased the amount of acetic acid and SCFAs in rats, thereby effectively hindering inflammation and organ damage in septic rats.